KEANEKARAGAMAN JENIS AMFIBI (ORDO ANURA) DI KAWASAN WISATA ALAM RIAM SOLAKNG KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Eva, Sesilia Agustina; Rifanjani, Slamet; Darwati, Herlina; Ramadhani, Endi; Deka, Elvy Quatrin (JURNAL HUTAN LESTARI, 2025)
Anura is an important component for the sustainability of ecosystems, namely as an important component in the food chain and environmental stability. The purpose of this study was to record the types of Anura found and to assess the level of Anura species diversity. This study was conducted in the Riam Solakng Nature Tourism Area, Sengah Temila District, Landak Regency. This study employed a survey method, utilizing the Visual Encounter Survey (VES) technique combined with a transect system. The results of the study showed 9 species from 4 families with a total of 129 individuals. The species diversity index H’ = 1.87 was categorized as moderate. The dominance index C = 0.18 was categorized as low. The species richness index Dmg = 1.65 was categorized as low. The species evenness index for aquatic habitats, E = 0.85, was categorized as high, and for terrestrial habitats, E = 0.94, was also categorized as high. Odorrana hossi had the highest relative abundance value at 30.23%, categorized as high, while Leptobrachium ingeri and Limnonectes kuhlii had low relative abundance values at 1.55%, categorized as low. The species similarity index between aquatic and terrestrial habitats is 36.36%, categorized as low. The highest encounter probability is for Odorrana hosii at 1.63 individuals per hour, while Leptobrachium ingeri and Limnonectes kuhlii have the lowest encounter probability at 0.08 individuals per hour. Keywords: Anura, Biodiversity, Riam Solakng. Abstrak Anura merupakan salah satu komponen penting bagi keberlangsungan ekosistem yaitu sebagai komponen penting dalam rantai makanan dan stabilitas lingkungan. Tujuan penelitian adalah mendata jenis-jenis Anura yang ditemukan dan mengkaji tingkat keanekaragaman jenis Anura. Penelitian ini dilaksanakan di Kawasan Wisata Alam Riam Solakng Kecamatan Sengah Temila Kabupaten Landak. Penelitian ini menggunakan metode survei, dengan teknik pengumpulan data Visual Encounter Survey (VES) dikombinasikan dengan sistem jalur. Hasil penelitian diperoleh 9 jenis dari 4 famili dengan total keseluruhan 129 individu. Nilai indeks keanekaragaman jenis H’= 1,87 terkategori sedang. Nilai indeks dominansi C = 0,18 terkategori rendah. Nilai indeks kekayaan jenis Dmg = 1,65 terkategori rendah. Nilai indeks kemerataan jenis habitat akuatik E= 0,85 terkategori tinggi dan habitat terestrial E= 0,94 terkategori tinggi. Odorrana hossi memiliki nilai kelimpahan relatif tertinggi yaitu 30,23% terkategori tinggi sedangkan Leptobrachium ingeri dan Limnonectes kuhlii memiliki nilai kelimpahan relatif rendah yaitu 1,55 % terkategori rendah. Nilai indeks kesamaan jenis antar habitat akuatik dan terestrial yaitu 36,36% terkategori rendah. Peluang perjumpaan paling besar yaitu Odorrana hosii 1,63 individu/jam sedangkan Leptobrachium ingeri dan Limnonectes kuhlii memiliki peluang perjumpaan paling kecil 0,08 individu/jam. Kata kunci: Anura, Biodiversitas, Riam Solakng.